Communication Behavior in the Transition to Endemic Phase - Adzhary Zilziani; Dini Rahmawati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the communication behavior of individuals during the pandemic and the transition phase to endemic when in the work environment. This pandemic has made several behavioral changes, especially communication behavior. The communication behavior studied includes interpersonal communication and group communication. This study uses a qualitative method. Data were collected through in-depth interviews and searches of various literature sources relevant to the theme of this research. As for the source of data / informants in this study is the community. This study uses the phenomenological approach of Alfred Schutz (1889-1959), namely phenomenology is connecting scientific knowledge with everyday experience, and from activities where experience and knowledge originate. Researchers look at how experiences occur in changes in individual communication behavior during the pandemic and after it from the informant's point of view. Experience and meaning that can be taken is the data that researchers get. The results of the study found that there were several changes in communication behavior in the transition phase to endemic.